How to make training sessions more effective / Mohamad Azmi Nias Ahmad and Nias Ahmad Abdul Ghani - Ahmad, Mohamad Azmi Nias; Abdul Ghani, Nias Ahmad (2006)
Effective training is not something that could be easily achieved. It requires combination of many elements, such as well-delivered lecture, participation from trainee, sharing of ideas between trainers and trainees, and trainers' ability to retain the subject matter. This paper presents discussions and recommendations that will assist trainers in making their training sessions effective.